2023
DOI: 10.1161/jaha.123.029738
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Predictors of 30‐Day Readmission in Patients With COVID‐19 and ST‐Segment–Elevation Myocardial Infarction in the United States: A Nationwide Readmission Database Analysis

Kunal N. Patel,
Monil Majmundar,
Tasveer Khawaja
et al.

Abstract: Background Rates, causes, and predictors of readmission in patients with ST‐segment–elevation myocardial infarction (STEMI) during COVID‐19 pandemic are unknown. Methods and Results All hospitalizations for STEMI were selected from the US Nationwide Readmissions Database 2020 and were stratified by the presence of COVID‐19. Primary outcome was 30‐day readmission. Multivariable hierarchical generalized logistic regression analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…COVID-19 patients had significantly shorter median times to readmission than non-COVID patients. The presented study conducted by Patel KN observed that the 30-day readmission risk factors were: chronic kidney disease, congestive heart disease, length of index hospitalization ≥ 5 days, and a low median household income [48][49][50][51].…”
Section: Discussionmentioning
confidence: 92%
“…COVID-19 patients had significantly shorter median times to readmission than non-COVID patients. The presented study conducted by Patel KN observed that the 30-day readmission risk factors were: chronic kidney disease, congestive heart disease, length of index hospitalization ≥ 5 days, and a low median household income [48][49][50][51].…”
Section: Discussionmentioning
confidence: 92%